One Fee, Two Reductions: The Double Abatement Effect of Pollutant Discharge Fees on Industrial Pollution and Carbon Emissions - Wang, Zhimeng; Yu, Lu; Zheng, Mengmeng; Xing, Yafei; Liu, Xiaoyuan; Wang, Yanwen; Xiao, Zumian (Frontiers in Environmental Science, 2022)
Formulating policies under the dual policy objectives of environmental protection and carbon neutrality in China is essential. This paper utilizes enterprise-level data to construct a panel model. Our empirical test indicates that increasing China’s pollutant discharge fee can effectively reduce industrial pollutants, including wastewater and exhaust gas. The empirical results indicate that in terms of enterprises, pollutant discharge fees can not only directly reduce carbon emissions but also indirectly by reducing coal assumption. This paper also constructs a threshold model of the carbon emission reduction effect of population size. It has been proved that when the population size does not exceed the threshold, the utility of the pollutant discharge fee is apparent. According to this study’s heterogeneity test, the carbon emission reduction effect of the pollutant discharge fee is more evident in large- and medium-sized enterprises and heavy pollution enterprises.